COVID-19 Infection and Professional Commitment Among Clinical Nurses: A Cross-Sectional Study of Work Stress and Social Support in Eastern Taiwan - Zhe-Ning Yu; Tai-Chu Peng (Nursing Reports, 2026)
Background/Objectives: Nurses in Taiwan faced markedly increased nurse-to-patient ratios and a high risk of occupational infection during the COVID-19 pandemic, generating considerable psychological and social strain. Professional commitment—reflecting nurses’ identification with, investment in, and intention to remain in the profession—is important for workforce retention and care quality, yet little is known about how contracting COVID-19 affects it. This study examined whether COVID-19 infection and the presence of long COVID symptoms were associated with professional commitment among clinical nurses, and identified sociodemographic, work-stress, and social-support correlates of commitment. Methods: A cross-sectional survey was conducted among registered nurses at a medical center in eastern Taiwan between 21 September 2023 and 28 February 2024. An anonymous electronic questionnaire assessed sociodemographic characteristics, COVID-19 infection/long-COVID status, work stress (Stress Scale for Healthcare Workers Caring for Patients with High-Risk Infectious Diseases), social support (Social Support Scale for clinical nurses), and professional commitment (Hospital Nurses’ Job Satisfaction and Professional Commitment Scale). Data from 364 valid responses (response rate 39.8% of the 914 nurses employed at the study hospital) were analyzed using independent-sample t-tests, Pearson correlation, one-way ANOVA, and multiple linear regression. Results: Professional commitment did not differ significantly by COVID-19 infection status (t = 0.50, p = 0.619) or by presence of long COVID symptoms (t = 0.85, p = 0.397). Social support was positively correlated with professional commitment (r = 0.261, p < 0.001), as was work stress, although the latter association was weak (r = 0.116, p = 0.027). Age, job rank, years of service, and education level were significantly associated with commitment (all p < 0.05). Multiple regression indicated that higher social support (B = 0.206, p < 0.001), greater work stress (B = 0.079, p = 0.006), and older age were independently associated with higher professional commitment (R2 = 0.297). Conclusions: In this cross-sectional sample, COVID-19 infection and long COVID symptoms did not appear to be associated with nurses’ professional commitment. Social support, age, and work stress emerged as the correlates most consistently related to commitment, with social support showing the largest association. Given the observational design and the retrospective measurement of work stress and social support, these findings should be regarded as preliminary and hypothesis-generating rather than conclusive. They tentatively indicate that workplace social support may merit further investigation as a potential avenue for sustaining nurses’ professional commitment during infectious disease outbreaks.